Family Planning Experiences and Needs of Young Women Living With and Without HIV Accessing an Integrated HIV and SRH Intervention in Zimbabwe-An Exploratory Qualitative Study - Constancia V. Mavodza; Constancia V. Mavodza; Joanna Busza; Constance R. S. Mackworth-Young; Constance R. S. Mackworth-Young; Rangarirai Nyamwanza; Portia Nzombe; Ethel Dauya; Chido Dziva Chikwari; Chido Dziva Chikwari; Mandikudza Tembo; Mandikudza Tembo; et al. (Frontiers Media S.A., 2022)
BackgroundPeople living with HIV have higher unmet family planning needs compared to those without HIV. This is heightened for young people. However, the provision of family planning for young people within HIV programmes is uncommon. We investigated family planning uptake, acceptability of, and engagement with a service offering integrated HIV and sexual and reproductive health services for youth in a community-based setting in Zimbabwe.MethodsCHIEDZA, a community-based intervention offering integrated HIV and sexual and reproductive health services to young people aged 16-24 years, is being trialed in Zimbabwe. This exploratory qualitative study was nested within an ongoing study process evaluation. Data was collected between March-May 2021 with two sets of interviews conducted: I) twelve semi-structured interviews with young women living with HIV aged 17-25 years and II) fifteen interviews conducted with young women without HIV aged between 20 and 25 years who used a contraceptive method. A thematic analysis approach was used.ResultsBefore engaging with CHIEDZA, young women had experienced judgmental providers, on account of their age, and received misinformation about contraceptive use and inadequate information about ART-contraceptive interactions. These presented as barriers to uptake and engagement. Upon attending CHIEDZA, all the young women reported receiving non-judgmental care. For those living with HIV, they were able to access integrated HIV and family planning services that supported them having broader sexual and reproductive needs beyond their HIV diagnosis. The family planning preference of young women living with HIV included medium to long-acting contraceptives to minimize adherence challenges, and desired partner involvement in dual protection to prevent HIV transmission. CHIEDZA's ability to meet these preferences shaped uptake, acceptability, and engagement with integrated HIV and family services.ConclusionsRecommendations for an HIV and family planning integrated service for young people living with HIV include: offering a range of services (including method-mix contraceptives) to choose from; supporting their agency to engage with the services which are most acceptable to them; and providing trained, supportive, knowledgeable, and non-judgmental health providers who can provide accurate information and counsel. We recommend youth-friendly, differentiated, person-centered care that recognize the multiple and intersecting needs of young people living with HIV.